The effectiveness comparison problem based learning model with NHT and TPS type on plane solid figure - Diana Amirotuz Zuraida; Karyati Karyati (Jurnal Riset Pendidikan Matematika, 2018)
The study was aimed to describe the learning model of problem based learning (PBL) with cooperative setting Numbered Heads Together (NHT) and Think Pair Share (TPS) type in terms of mathematics learning achievement, reflective thinking skills, and self regulated learning of junior high school 8th grade students. The study was a quasi experimental research with pretest-posttest non-equivalent group design. The sample were taken at random from five classes, consisted  of VIII-A and VIII-C. Data were analyzed by using multivariate statistical using Multivariate Analysis of Variance (MANOVA). The result of the study at 5% level significance indicated that PBL with cooperative setting TPS type was effective in terms of reflective thinking skill; there was no difference of the effectiveness between PBL with cooperative setting NHT type and PBL with cooperative setting TPS type in terms of achievement, reflective thinking skills, and self-regulated learning of junior high school 8th grade students.